Developing cold-adapted biomass for the anaerobic treatment of domestic wastewater at low temperatures (4, 8 and 15 °C) with inocula from cold environments. (1st April 2017) - Petropoulos, Evangelos; Dolfing, Jan; Davenport, Russell J.; Bowen, Emma J.; Curtis, Thomas P.
Abstract: Temperature is the bottleneck for the anaerobic treatment of domestic wastewater in temperate climates. Most previous attempts to achieve anaerobic treatment at low temperatures have attempted to acclimatize mesophilic sludge and have failed at temperatures below 10–13 °C. We describe an alternative approach using communities from environments that have been exposed to low temperatures over evolutionary time-scales as seed for such reactors. Batch reactors were inoculated with a mixture of soils and sediments from the high Arctic and an Alpine lake to treat UV-sterilized raw domestic wastewater at 4, 8 and 15 °C. To evaluate the intrinsic treatment capacity of the bacteria the specific rates of methanogenesis and hydrolysis were evaluated. Specific methanogenic activity at 4, 8 and 15 °C was 6.3, 7.6 and 10.3 fmol CH4 cell −1 day −1 respectively. Specific putative hydrolysis rates were 76.2, 186.6 and 251.9 fgrams COD cell −1 day −1 . Hydrolysis was twice as temperature sensitive as methanogenesis (Q10 : 4.62 and 1.57 respectively). The specific rates are over ten times higher than we have previously observed in microcosms fed with settled wastewater at the same temperatures. The results imply that inoculating reactors with cold-adapted communities is a promising way to develop biomass capable of treating anaerobic wastewater treatment at low temperatures whilst achieving an effluent that conforms to the EC Directive COD standards. Large-scale reactors are feasible if satisfactory cell concentrations can be achieved. Graphical abstract: Highlights: Arctic soils and alpine lake sediments were used as seed to develop psychrophilic biomass. Biomass is capable of treating anaerobically raw domestic wastewater at ≤4 °C was developed. Cell specific activity used to evaluate the properties of the biomass and prospects for scale up. Methanogenesis is less temperature sensitive than hydrolysis in the adapted biomass. Hydrogenotrophic methanogenesis plays a key role at lower temperatures.